Re-engineering your business - Morris, Daniel C. (McGraw-Hill, 1993)
Reengineering's new methodologies for business process improvement are much in demand with managers in every industry. This resource explains the whats, whys and hows of business reengineering. Comprehensive and pragmatic, this guide shows managers how to stimulate performance by stripping their business down to the essentials. Then it shows them how to rebuild - piece by piece - around a customer focus, so that each process adds value to the product and enhances competitive potential. The book also details how to apply recent breakthroughs in systems analysis, computer modelling, and simulation techniques to the process of business redesign and restructuring, without impeding day-tp-day operations.